HEXAGONAL HONEYCOMB PL-GaN NANOSHEET AS ADSORBENT SURFACE FOR GAS MOLECULES SENSING: A QUANTUM CHEMICAL STUDY - MOLLAAMIN, FATEMEH; MONAJJEMI, MAJID (World Scientific Pub Co Pte Ltd, 2023)
Regarding two-dimensional (2D) nanomaterials as gas sensors, we have studied the adsorption of gas molecules (NH3, NO2, NO) on the graphitic GaN sheet (PL-GaN) using density functional theory calculations. “Langmuir” adsorption of gas molecules of NH3, NO2, and NO on the graphitic GaN sheet has been accomplished using density functional theory. The changes in charge density have shown a more important charge transfer on the hexagonal honeycomb nanosheet of gallium nitride (GaN) which acts as the electron acceptor while gas molecules act as the stronger electron donors through adsorption on the graphitic-like GaN surface. The adsorption of NH3, NO[Formula: see text] and NO, respectively, on GaN nanosheet has more contribution with high expansion curves of hydrogen, nitrogen and oxygen. The results extracted from PDOS curves after optimization show the electron transferring from nitrogen and oxygen of gas molecules (adsorbate/donor) towards gallium in the active site of GaN surface (adsorbent/acceptor). GaN nanosheet represents enough capability for adsorbing gases of NH3, NO2, and NO through charge transfer from nitrogen and oxygen atoms to the gallium atom regarding the intra-atomic and interatomic interactions. Concerning the change of physicochemical properties of the PL-GaN sheet before and after molecule adsorption, the PL-GaN nanosheet can be applied as an appropriate selective gas sensor for NH3, NO2and NO detection.
Keywords: 7. Clean energy